Respuesta :

(-2,2)(2,-2)
slope = (-2 - 2) / (2 - (-2) = -4/4 = -1

as far as point slope form, there can be 2 answers...

y - y1 = m(x - x1)
slope(m) = -1
using points (-2,2)...x1 = -2 and y1 = 2
now we sub
y - 2 = -1(x - (-2) =
y - 2 = -1(x + 2) <== or could be written as y - 2 = - (x + 2)

y - y1 = m(x - x1)
slope(m) = -1
using points (2,-2)...x1 = 2 and y1 = -2
now we sub
y - (-2) = -1(x - 2) =
y + 2 = -1(x - 2) <== or can be written as y + 2 = - (x - 2)

either one of those answers is ur point slope form